What is the Mishnah? : the state of the question : the proceedings of a conference at Harvard University - Cohen, Shaye J. D. (Cambridge Harvard University Center for Jewish Studies, 2022)
The Mishnah is the foundational document of rabbinic Judaism--rabbinic law is based on the Talmud which, in turn, is based on the Mishnah. Yet its sources, genre, and purpose are obscure. What Is the Mishnah? collects papers by leading scholars from the United States, Europe, and Israel and gives a clear sense of the direction of Mishnah studies
The Mishnah and the Bible / Tzvi Novick -- The Mishnah and Ancient Near Eastern Law / Jonathan S. Milgram -- The Mishnah and the Dead Sea Scrolls / Vered Noam -- Mishnah and Tosefta / Shamma Friedman -- The Literary Evolution of the Mishnah / Yair Furstenberg -- The Presentation of the Past in the Mishnah / Martin Goodman -- The Mishnah and Roman Law : A Rabbinic Compilation of ius civile for the Jewish civitas of the Land of Israel under Roman Rule / Catherine Hezser -- Mishnah and History / Hayim Lapin -- The Rhetoric of the Mishnah / Beth A. Berkowitz -- Mishnah as Utopia / Naftali S. Cohn -- Mishnah and Halakhah / Moshe Halbertal -- Nomos and Mishnah : The Turn to Narrative in Recent Mishnah Scholarship / Moshe Simon-Shoshan -- Holiness in the Mishnah / Sarit Kattan Gribetz -- The Language of the Mishnah--Between Late Hebrew and Mishnaic Hebrew / Elitzur A. Bar-Asher Siegal -- Priests and Pietists in the Mishnah / Jonathan Klawans -- Mishnah, Women, Gender : What Are We Reading For, Where Are We Reading It? / Gail Labovitz -- Goyim in the Mishnah / Ishay Rosen-Zvi -- "And Your People Are All Righteous" : Heretics and Heresy in the Mishnah / Adiel Schremer -- The Halakhic Midrashim and the Canonicity of the Mishnah / Azzan Yadin-Israel -- The Publication and Early Transmission of the Mishnah / David Stern -- The Reception of the Mishnah from the Geonic Period to the Age of Print / Uziel Fuchs -- The Reception of the Mishnah in the Modern Era / Chanan Gafni.
Proceedings of a series of remote workshops co-sponsored by the Julis-Rabinowitz Program on Jewish and Israeli Law and the Center for Jewish Studies at Harvard University in 2021
Includes bibliographical references and index
Description based on online resource; title from PDF title page (De Gruyter, viewed on June 7, 2023)
JSTOR
Keywords: Mishnah -- Criticism, interpretation, etc. -- Congresses; Mishnah; RELIGION / Judaism / History; proceedings (reports); Criticism, interpretation, etc; Conference papers and proceedings; Actes de congrès.